The peculiarities of organizational socialization among newcomers with different work experience - Žukauskaitė, Irena; Bagdžiūnienė, Dalia (Psichologija, 2008)
The aim of this study was to discover if there are any differences among organizational socialization of newcomers who already have work experience and employees who are new in labour market. And if the differences were found, to establish what organizational factors have the biggest impact on them. 71 participants took part in the study: 33 participants were working in the first jobs, 38 were working in the second or later jobs. Participants fill out the questionnaires at the end of the 3rd month within the organization. They were asked to evaluate their knowledge about the organization, the amount of experienced of work related anxiety, their attitudes towards the organization they work and towards their job, and the position in newcomer – seniority continuum (feeling of being real member of organization). Additionally they were asked to evaluate leadership style of their executives, quality of leader-subordinate relationship, organizational culture and work group climate. Work group size and mentorship system in organization were the variables which also were taken into analysis. As distinct from other surveys, the results showed no correlation between the work related anxiety and other parameters of organizational socialization. Should the longitudinal studies fail to prove the lack of correlations to be the result of unlinear dependability between time spent in organization and lessen job related anxiety, other emotional adjustment measures are to be considered. Despite the fact that newcomers with and without work experience equally rate themselves in newcomer – seniority continuum, this evaluation is the result of different issues. Those who start their work career have much more information about organization (Mann Whitney z = –1.98, p = 0.047) but still they feel stronger anxiety (Mann Whitney z = –2.29, p = 0,022) than those who already have work experience. The analysis of the organizational factors which affect new employee socialization suggests that the size of newcomer’s work group is negatively related to the results of organizational socialization – the bigger the work group, the worse the organizational socialization (regression analysis R = 0.492, R2 = 0.242, p = 0.000). The better leader – member Exchange evaluations, the more favourable group climate, the help of the official mentor during the first months working in organization, the mild exposure of innovative organizational culture, on the other hand, leads to better results of the organizational socialization (stepwise regression analysis R = 0.734, R2 = 0.539, p = 0.000). Yet again different factors contribute differently to the quality of new employee socialization when newcomers with and without previous work experience were analyzed separately. The results add more arguments for the individualized organizational socialization theory vs. collective one.
Keywords: new employee; organizational socialization; socialization factors; work experience